Household survey data of integrated land and water management for adaptation to climate variability and change in West Africa - Mwungu, Chris Miyinzi; Kizito, Fred; Mwongera, Caroline; Koech, Nicholas; Odhiambo, Collins (International Center for Tropical Agriculture, 2019)
This data was collected in seven west African countries namely Nigeria, Burkina Faso, Sierra Leone, Benin, Gambia and Senegal. In 2012, the Danish government funded seven projects in west Africa to help small scale farmers adapt to the negative effects of climate change. These projects were implemented by West and Central African Council for Agricultural Research and Development (CORAF/WECARD). In 2018, the International Center for Tropical Agriculture (CIAT), International Water Management Institute (IWMI) and International Food Policy Research Institute (IFPRI) were commissioned by the world bank to evaluate the results and impact of these projects. The main objective of collecting this data was to conduct an impact assessment, identify success stories of the seven projects and identify site specific land and water management practices that can be scaled out to enhance farmer’s resilience to climate change and variability.